Peculiarities of the formation of scincillation response in organic materials with stochastic character of light propagation - Polupan, Ya.I.; Lazarev, I.V.; Martynenko, E.V.; Minenko, S.S.; Tarasenko, O.A.; Тarasov, V.A. (Problems of Atomic Science and Technology, 2023)
The paper examines the possibility of using an organic polycrystal as the “opaque” scintillator. Polycrystals are produced by pressing crystalline grains. When light propagates through a polycrystal, it is repeatedly reflected and refracted at the boundaries of the grains. This makes its propagation difficult. We studied the light output and optical transmittance of stilbene and p-terphenyl polycrystals with different fractions of crystalline grain: from 0.06…0.1 to 2.0…2.5 mm (the samples 20 mm in diameter and 2 mm in height) was conducted. Modelling of light propagation in polycrystalline samples of stilbene and p-terphenyl was carried out and the values of the light collection coefficients were calculated. It was found that in order to obtain the polycrystalline samples with sufficiently high light output and high efficiency of detection of local sites of interaction of ionizing radiations, grains in the range of 0.4…0.8 mm should be used. Досліджується можливість використання органічного полікристалa в якості “мутного” сцинтилятора. Полікристали виготовляють методом пресування кристалічних гранул. Світло при розповсюдженні крізь полікристал зазнає багаторазового відбивання та заломлення на границях гранул, що ускладнює його проходження. Проведено дослідження світлового виходу та оптичного пропускання полікристалів стильбену та п-терфенілу із різними фракціями кристалічних гранул: від 0,06…0,1 до 2,0…2,5 мм (діаметр зразків 20 мм та висота 2 мм). Проведено моделювання проходження світла в полікристалічних зразках стильбену та п-терфенілу, та розраховані значення коефіцієнтів світлозбирання в них. З’ясовано, що для отримання полікристалічних зразків із достатньо високим світловим виходом та високою ефективністю виявлення локальних місць взаємодії іонізуючого випромінювання слід використовувати гранули в діапазоні 0,4…0,8 мм.